A farewell to critical junctures: Sorting out long-run causality of income and democracy - Erich Gundlach; Martin Paldam (University of Aarhus, School of Economics and Management, 2008)
We consider the empirical relevance of two opposing hypotheses on the causality between income and democracy: The Democratic Transition claims that rising incomes cause a transition to democracy, whereas the Critical Junctures hypothesis denies this causal relation. Our empirical strategy is justified by Unified Growth Theory, which hypothesizes that the present international income differences have roots in the prehistoric past. Thus, we use prehistoric measures of biogeography as instruments for modern income levels, and find a large long-run causal effect of income on the degree of democracy. This result rejects the Critical Junctures hypothesis, which is an important part of the Primacy of Institutions view.
Keywords: B25; O1; 330; democracy; unified growth theory; biogeography; Long-run growth; Wirtschaftswachstum; Wachstumstheorie; Demokratisierung; Evolutionsökonomik; Ökonomische Theorie der Demokratie